2022
DOI: 10.3390/pharmaceutics14102045
|View full text |Cite
|
Sign up to set email alerts
|

Structurally Modified Bioactive Peptide Inhibits SARS-CoV-2 Lentiviral Particles Expression

Abstract: Coronavirus disease 2019 (COVID-19), the current global pandemic is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Various pharmaceuticals are being developed to counter the spread of the virus. The strategy of repurposing known drugs and bioactive molecules is a rational approach. A previously described molecule, Ile-Arg-Trp (IRW), is a bioactive tripeptide that exhibits an ability to boost angiotensin converting enzyme-2 (ACE2) expression in animals and cells. Given the importance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…IRW, an animal protein-derived peptide, may inhibit the interaction of spike (S) protein of SARS-CoV-2 with ACE2 and have greater contact with RBD. Cellular assays have demonstrated that IRW can inhibit the expression of SARS-CoV-2 S protein and ACE2 ( 14 ). With the characteristics of designability, strong stability, small volume, and easy absorption, peptides from animal proteins can be combined with nanomaterials for targeted therapies.…”
Section: Introductionmentioning
confidence: 99%
“…IRW, an animal protein-derived peptide, may inhibit the interaction of spike (S) protein of SARS-CoV-2 with ACE2 and have greater contact with RBD. Cellular assays have demonstrated that IRW can inhibit the expression of SARS-CoV-2 S protein and ACE2 ( 14 ). With the characteristics of designability, strong stability, small volume, and easy absorption, peptides from animal proteins can be combined with nanomaterials for targeted therapies.…”
Section: Introductionmentioning
confidence: 99%